To determine whether \( x = -3 \) is a solution to the quadratic equation \( -3x^2 - 9x = 0 \), we can substitute \( x = -3 \) into the equation and evaluate.
Starting with the equation:
\[ -3x^2 - 9x = 0 \]
Substituting \( x = -3 \):
\[ -3(-3)^2 - 9(-3) = 0 \]
Calculating:
- Compute \( (-3)^2 = 9 \).
- Substitute this value into the equation:
\[ -3(9) - 9(-3) = 0 \]
- Simplify:
\[ -27 + 27 = 0 \]
This simplifies to:
\[ 0 = 0 \]
Since both sides of the equation are equal, \( x = -3 \) is indeed a solution.
The correct response is:
Yes, x = -3 is a solution because substituting it back into the equation results in the following:
\[ -3(-3)^2 - 9(-3) = 0 \Rightarrow 0 = 0 \text{ (True)} \]